Analysis of Platelet Volume Indices and their utility in Acute Coronary Syndrome - Aadil Ahmed Mir; Afaq Ahmed Khan; Jan Mohd Sheikh; Mohd Iqbal Dar; Hilal Ahmed Rather; Aijaz Ahmed Lone; Imran Hafeez; Aamir Rashid (Heart Views)
Background: Higher Mean Platelet Volume (MPV) may become useful marker for early detection and prognostication of Acute Coronary Syndrome (ACS) along with other biomarkers. Aim of the Study: To study and analyse platelet volume indices (PVI) in ACS patients. Material and Methods: The blood samples of patients diagnosed as acute coronary syndrome were analysed and complete blood count analysis were done including PVI. The PVI of different groups of acute coronary syndromes were compared with each other and to age and sex matched healthy controls. Results: The mean MPV of ACS group was 11.2±1.45 fL and was significantly higher than control group 8.9±1.12 fL. Among ACS cases mean MPV of STEMI was 11.51±1.44fL, in NSTEMI it was 10.83±1.51fL and in unstable angina (UA) it was 9.21±1.36 fL. Significantly higher in STEMI followed by NSTEMI than unstable angina. The mean PDW of ACS cases was 18.2±1.52fL and was significantly higher than control group 16.8±1.28fL. Among ACS cases it was significantly higher in STEMI 18.37±1.48fL than NSTEMI 17.91±1.46fL and it was significantly higher than UA group 17.04±1.88 fL. The mean PCT of ACS cases was 0.231±0.042% was significantly higher than controls 0.173±0.023%. Conclusion: PVI provides an important, simple, effortless, and cost-effective tool, which can be useful in predicting and prognosticating an acute coronary event. MPV and PDW has the potential to be used as a preliminary test to identify high-risk patients for myocardial infarction.